Relationships between hydrogen bonds and halogen bonds in biological systems. Issue 2 (1st April 2017) - Rowe, Rhianon K.; Ho, P. Shing
Abstract : The competitive and orthogonal relationships between halogen bonds and the more ubiquitous hydrogen bond are reviewed, focusing on how these affect the structure of biological molecules and protein–ligand complexes. Abstract : The recent recognition that halogen bonding (XB) plays important roles in the recognition and assembly of biological molecules has led to new approaches in medicinal chemistry and biomolecular engineering. When designing XBs into strategies for rational drug design or into a biomolecule to affect its structure and function, we must consider the relationship between this interaction and the more ubiquitous hydrogen bond (HB). In this review, we explore these relationships by asking whether and how XBs can replace, compete against or behave independently of HBs in various biological systems. The complex relationships between the two interactions inform us of the challenges we face in fully utilizing XBs to control the affinity and recognition of inhibitors against their therapeutic targets, and to control the structure and function of proteins, nucleic acids and other biomolecular scaffolds.